2022
DOI: 10.1038/s41586-022-04570-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear control of transcription through enhancer–promoter interactions

Abstract: Chromosome structure in mammals is thought to regulate transcription by modulating three-dimensional interactions between enhancers and promoters, notably through CTCF-mediated loops and topologically associating domains (TADs)1–4. However, how chromosome interactions are actually translated into transcriptional outputs remains unclear. Here, to address this question, we use an assay to position an enhancer at large numbers of densely spaced chromosomal locations relative to a fixed promoter, and measure promo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
204
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(235 citation statements)
references
References 67 publications
31
204
0
Order By: Relevance
“…2b,c ) (see also below). Collectively these results support other recent data that the relationship between gene activity and E-P contact frequencies is non-linear and that subtle changes in contact frequencies can lead to large changes in expression 36 , 45 , 46 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2b,c ) (see also below). Collectively these results support other recent data that the relationship between gene activity and E-P contact frequencies is non-linear and that subtle changes in contact frequencies can lead to large changes in expression 36 , 45 , 46 .…”
Section: Resultssupporting
confidence: 90%
“…We propose this is a consequence of concentrated loop extrusion activity. We, like others, find that transcriptional activity is controlled by more than just E-P contact frequencies 36 , 45 , 46 . Preformed contacts established prior to gene activation have been observed at, for example, the Hoxd locus, and such ‘permissive’ structures 58 may be reminiscent of the topologies that we detect here.…”
Section: Discussionsupporting
confidence: 75%
“…Besides boundary insulation, we observe that enhancer–promoter communication may be influenced by genomic distances. Indeed, analyses in mESCs demonstrated that the transcriptional output depends on the genomic distance between an enhancer and its promoter 44 . Moreover, reduced distances between the ZRS enhancer and the Shh gene, in inverted alleles, can overcome boundary insulation and cause gene activation 45 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern is followed by the promoter's transcriptional output, where transcriptional levels decrease with increasing genomic distance and fall to promoter-only levels when the enhancer is located outside of the TAD and is not able to activate the promoter. Therefore, the authors built a mathematical model to explain transcriptional output in terms of contact probabilities: Transcription is described by a two-state (on–off) model where the frequency of transcriptional bursts depends on the enhancer-promoter contact probability through a Hill function [169] .…”
Section: Discussionmentioning
confidence: 99%